Implementation of Structured Object-Oriented Formal Language for Warehouse Management System - Afifudi, Irfin; Martina, Inge (CommIT (Communication and Information Technology) Journal, 2020)
Designing process is inseparable from software development. Like other software development processes, designing process faces many problems, such as improper and ambiguous specifications. These problems may be overcome by applying formal engineering methods. One of which is Structured Object-Oriented Formal Language (SOFL). The analysis and formation of the design and implementation of SOFL are carried out as a solution to the problem. The application of SOFL is divided into three parts according to SOFL rules, namely informal specification, semi-formal specification, and formal specification. The design and implementation are measured and tested using rigorous review and maintainability index. This research uses a warehouse management system, a safety-critical system, as a case study. Rigorous analysis shows that SOFL in warehouse management system increases the maintainability index of 56.94%. It means that it is easier to develop.